Recombinant ostreolysin (rOly) inhibits the anti-adipogenic Hedgehog (Hh) signaling pathway in 3T3-L1 cells. (August 2019) - Israeli, Erez; Adler Berken, Nastacia; Gover, Ofer; Waechtershaeuser, Eike; Graeve, Lutz; Schwartz, Betty
Graphical abstract: We recently generated a recombinant version of the 15 kDa fungal protein Ostreolysin (rOly) which has been previously shown to induced brown-like phenotype in brown pre-adipocyte HIB-1B In-vitro and protect against high-fat diet induced nonalcoholic fatty liver disease in mice In-vivo. Herein, we demonstrate that rOly induced distinct morphological changes in white pre-adipocyte 3T3-L1 and human adipose-derived stem cells. At the molecular level, our results demonstrate that rOly affect tubulin post-translation modification in a cell dependent manner and inhibit the anti-adipogenic pathway Hedgehog signaling independent to AMPK activation. Point mutations on tryptophan residues showed the importance of rOly membrane interaction to address the effect on morphological and Hedgehog signaling pathway. In conclusion, our results shed light on rOly molecular mechanism in a different types of adipocyte cells. Highlights: rOly inhibits SAG induced Hedgehog (Hh) signaling pathway in 3T3-L1. rOly modifies protein expression levels of acetylated tubulin and its intracellular distribution in HIB-1B cells. rOly affects various genes levels mediated by AMP-activated protein kinase (AMPK) phosphorylation in 3T3-L1 cells. Abstract: Obesity is a nutrition-associated disorder result of an imbalance between energy intake and energy expenditure. Changing adipocytes differentiation patterns is considered as a strategy to treat obesity-related disorders. Recently, much interest is focused on the role of posttranslational modifications of tubulin on adipocyte differentiation. We recently demonstrated that a recombinant version of the fungal protein Ostreolysin (rOly) drastically affects metabolism of adipose tissue. The aim of the present study is to extend our understanding of the in vitro effects of rOly on different adipocytes. We demonstrate that rOly inhibits the anti-adipogenic Hedgehog (Hh) signaling pathway in 3T3-L1 cells. Additionally, rOly affected the gene expression levels of SQSTM1 and Collagen type 1, which are mediated by AMP-activated protein kinase (AMPK) activity in 3T3-L1 cells. We provide a potential molecular mechanistic approach describing that the effect of rOly on adipocytes is mediated by tubulin acetylation and AMPK phosphorylation.